Role of proline peptide bond isomerization in unfolding and refolding of ribonuclease. - Schmid, F X (1986)
The isomerization of the proline peptide bond between tyrosine-92 and proline-93 in bovine pancreatic ribonuclease A has been investigated in the unfolded protein as well as during the slow refolding process. This bond is in the cis state in the native protein. By comparison of various homologous ribonucleases we show that isomerization of proline-93 is associated with a change in fluorescence of tyrosine-92. This provides a spectroscopic probe to monitor this process in the disordered chain after unfolding as well as its reversal in the course of slow refolding. In unfolded ribonuclease incorrect trans isomers of proline-93 are found in both slow-folding species. trans----cis reversal of isomerization of this proline peptide bond during refolding shows kinetics that are identical with the time course of formation of native protein. Isomerization of proline-93 is slower than the formation of a native-like folded intermediate that accumulates on the major slow refolding pathway. Models to explain these results are discussed.